2019
DOI: 10.1109/access.2019.2901128
|View full text |Cite
|
Sign up to set email alerts
|

Local and Global Randomized Principal Component Analysis for Nonlinear Process Monitoring

Abstract: Kernel principal component analysis (KPCA) has been widely used in nonlinear process monitoring since it can capture the nonlinear process characteristics. However, it suffers from high computational complexity and poor scalability while dealing with real-time process monitoring and large-scale process monitoring. In this paper, a novel dimension reduction technique, local and global randomized principal component analysis (LGRPCA), is proposed for nonlinear process monitoring. The proposed LGRPCA method first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…This is because both approaches entail differentiating the statistical index, which is difficult if the chain involves a kernel function [86]. Nevertheless, many researchers have derived analytical expressions for either kernel contributions-based diagnosis [66,79,81,83,87,94,119,127,133,136,146,150,156,157,162,164,194,213,241,268,275,276,278,279,288,289,293] or kernel reconstructions-based diagnosis [86,117,140,155,161,163,176,217,236,254,265,285]. However, most derivations are applicable only when the kernel function is the RBF, Equation (5).…”
Section: Diagnosis By Fault Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because both approaches entail differentiating the statistical index, which is difficult if the chain involves a kernel function [86]. Nevertheless, many researchers have derived analytical expressions for either kernel contributions-based diagnosis [66,79,81,83,87,94,119,127,133,136,146,150,156,157,162,164,194,213,241,268,275,276,278,279,288,289,293] or kernel reconstructions-based diagnosis [86,117,140,155,161,163,176,217,236,254,265,285]. However, most derivations are applicable only when the kernel function is the RBF, Equation (5).…”
Section: Diagnosis By Fault Identificationmentioning
confidence: 99%
“…It was adopted recently by Yu et al [277] for kernel CCA. Meanwhile, random Fourier features was adopted by Wu et al [279] for kernel PCA. This scheme exploits Bochner's theorem [59,279], in which the kernel mapping is approximated by passing the data through a randomized projection and cosine functions.…”
Section: Fast Computation Of Kernel Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…A ductile fracture occurs when the soldering alloy is exposed to plastic deformation due to stress caused by damage including excessive tensions such as thermal variation or mechanical effort. In some research [6][7][8][9][10][11][12][13], it is mentioned that mechanical effort causes parallel cracks, and thermal variation generates a network of multiple fissures. Furthermore, there have been fracture analyses using measures of resistance and visual inspection.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this, there have been development tests that determine the capacity of a soldering alloy to resist thermal fatigue. Li et al [7], Wu et al [8], and Cheg [14] mentioned that electronic systems are a dynamic object susceptible to vibration. Their investigations demonstrated that a soldering alloy is a place of failure caused by vibrations.…”
Section: Introductionmentioning
confidence: 99%